Comparison of rowing on a Concept 2 stationary and dynamic ergometer - Benson, A.; Abendroth, J.; King, D.; Swensen, T. (Journal of Sports Science & Medicine, 2011)
Biomechanical and physiological responses to rowing 1000 m at a power output equivalent to a 2000 m race were compared in 34 collegiate rowers (17 women, 17 men) rowing on a stationary and dynamic Concept 2 ergometer. Stroke ratio, peak handle force, rate of force development, impulse, and respiratory exchange ratio decreased by 15.7, 14.8, 10.9, 10.2 and 1.9%, respectively, on the dynamic ergometer. In contrast, percent time to peak force and stroke rate increased by 10.5 and 12.6%, respectively, during dynamic ergometry; the changes in stroke rate and impulse were greater for men than women. Last, VO2 was 5.1% higher and efficiency 5. 3% lower on the dynamic ergometer for men. Collegiate rowers used higher stoke rates and lower peak stroke forces to achieve a similar power output while rowing at race pace on the dynamic ergometer, which may have increased the cardiopulmonary demand and possibly reduced force production in the primary movers. Differences were more pronounced in males than females; this dichotomy may be more due to dynamic ergometer familiarity than sex.